Sage without a Stage: Expanding the Object of Teaching in a Web-Based, High-School Classroom - Murphy, Elizabeth; Rodriguez-Manzanares, Maria A. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
This paper reports on a study that uses cultural historical activity theory (CHAT) to make sense of e-teachers’ activity in a context of high-school distance education. Data collection involved semi-structured interviews with 13 e-teachers as well as seven management and support personnel in an organization responsible for the design and delivery of high-school distance education in the province of Newfoundland and Labrador, Canada. As well, the authors conducted a second round of interviews with 12 of the 13 teachers. Findings revealed that the traditional metaphor of teacher as ‘sage on the stage’ ceased to have a reference point in the distributed online classroom. The e-teachers were widening the object of their activity to include less teacher-centered forms of learning that involved more student independence.